THE EFFECT OF USING FRAYER MODEL ON STUDENTS’ VOCABULARY MASTERY - Ellis Ekawati Nahampun (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2014)
This study was conducted as an attempt to find out the effect of using Frayer Model on Students’ Vocabulary Mastery. This study used the experimental design. The population of this study was the students of SMA Parulian 1 Medan. There were sixty students of first grade senior high school as the sample of the research. This study was conducted with two randomized groups namely experimental group and control group. The control group was taught by conventional method while experimental group was taught by using Frayer Model. The instrument of collecting data was objective multiple choice test which consisted of 40 items. To obtain the reliability of the test, the researcher used Kuder-Richardson (KR-20) formula. The calculation shows that the reliability was 0.73 (high). The data were analyzed by using t-test. The calculation shows that t-observed (5.41) is higher than t-table (2.00) at the level of significance (α) 0.05 with the degree of freedom (df) 58. Therefore, null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that teaching vocabulary by using Frayer Model has more significant effect than teaching vocabulary by using conventional method.   Keywords: Vocabulary, Students’ Vocabulary Mastery, Frayer Model